Framework and Evolution of Next Generation Union Video Service - Xinhai Hua; Yaodong Liu; Huoshun Xu (Dianxin kexue)
With the explosive growth of IPTV and OTT,how to integrate the video platform with low cost,high performance and intensive is a big problem need to be solved,and the platform can achieve reasonable optimization of system resources and network.Next generation union video service architecture was proposed.The flat and fully union system can reduce the cost of maintenance to the maximum extent,proving and unifying the user experience,easy to integrate many kinds of services and bring more business prospects for the video service.